The Evolution of Sectoral Risk Return Profiles in the Indonesian Stock Market: Evidence from 2023–2026 - Khairun Amala (CERED Indonesia Institute, 2026)
This paper reviews the formation of sectoral risk-return profiles of the Indonesian stock market for 2023-2026. This research is a quantitative descriptive comparative study that explains the Jakarta Composite Index and IDX sectoral indices in terms of return, risk, risk-adjusted performance, and sectoral positioning. Data were collected from publications of Indonesia Stock Exchange and processed by Excel and R software. The results show that the sectoral investment attractiveness was dynamic, not static. The Jakarta Composite Index was a useful market benchmark, but it did not fully reflect the sectoral differences. Energy, Properties & Real Estate, Healthcare and Infrastructures displayed relatively efficient risk-adjusted profiles over the entire observation period. Yet, the annual results revealed that sectoral attractiveness varied according to market phases. Technology was the best performing sector in 2025 and Industrials had an exceptional position in the interim period of 2026. This study adds to the literature by proposing the Sectoral Investment Positioning Matrix, a practical framework for understanding the concepts of sectoral repositioning, sector rotation, portfolio allocation, and risk management, in an emerging market context.